Analysis of students' cognitive physics learning outcomes on the material of substances and their forms using think-pair-share - Taihuttu, Jony; Batlolona, John Rafafy; Wattimena, Herman Semuel; Jamaludin, Jamaludin; Silahooy, Stevi; Akyuwen, Frandy (Pascasarjana, Mataram University, 2024)
In the last decade, many studies of physics learning at the junior high school level seem to show that student-centered interactions have a greater effect than teacher-centered interactions in improving physics learning outcomes. Based on this premise,Think-pair-share (TPS) which is one type of cooperative learning model developed by Frank Lyman and his colleagues from the University of Maryland (1981) is a teaching strategy that promotes active and collaborative learning; however, its effectiveness and application are very good in physics learning. The purpose of this study is to analyze student learning outcomes using the TPS type cooperative model on the material of substances and their forms. This study uses a descriptive model with 24 students as subjects divided into four groups. The implementation of the study on SMP Xaverius Passo. Data were collected through tests, namely pretest and posttest and observations using student worksheets and affective and psychomotor assessments of students. The results showed that there was a significant increase in student learning outcomes after the implementation of the TPS model, both from cognitive, affective, and psychomotor aspects. This study recommends the use of the TPS cooperative learning model as a solution to improve the quality of physics learning in schools